Behavior Propagation of Surge Tsunami in Casuarina Equisetifolia Forest - Novi Andhi Setyo Purwono; Nizam (International Journal of Marine Engineering Innovation and Research, 2026)
The tsunami disaster in the Indian Ocean on 26 December 2004 had an impact that killed more than 300,000 worldwide and caused catastrophic damage to infrastructure. Indonesia is a tsunami-prone country because it is located between two plates that have great potential for collision, that are the Eurasian plate and the Indo-Australian plate. One of the efforts to mitigate the tsunami disaster is to create protection in the form of natural protection (coastal forests). Tsunamis that move closer to the coast are in the form of surge waves similar to waves resulting from a dam break. The change in depth from the deep sea towards the coast results in an increase wave height, but a decrease in wave velocity. This research was conducted using a physical model simulation approach in the laboratory, using a dam break-based tsunami wave generation method by making a simulation of the flume used measuring 16.80 m x 1.0 m x 0.8 m equipped with a dam break gate. Making a model of a casuarina forest is done by observing and measuring tree dimensions, plant spacing and density. The research results show that there was a decrease in water velocity for the tsunami model d0 = 60 cm for the model without canopy 1 m is 21.09%, 2 m is 29.36%, and 3 m is 36.50%. The decrease surge velocity due to the model with canopy 1 m is 21.71 %, 2 m is 29.67 %, and for 3 m is 40.40 %. For the velocity function to be changed to f V (m, L, n, x). The tree canopy effect is quite effective for high tsunamis but for low tsunami it is not effective, because the tsunami surge will propagate through the tree trunks below canopy.